2017
DOI: 10.1038/cgt.2017.4
|View full text |Cite
|
Sign up to set email alerts
|

Customized laboratory TLR4 and TLR2 detection method from peripheral human blood for early detection of doxorubicin-induced cardiotoxicity

Abstract: Cancer treatments can have significant cardiovascular adverse effects that can cause cardiomyopathy and heart failure with reduced survival benefit and considerable decrease in the use of antineoplastic therapy. The purpose of this study is to assess the role of TLR2 and TLR4 gene expression as an early marker for the risk of doxorubicin-induced cardiomyopathy in correlation with early diastolic dysfunction in patients treated with doxorubicin. Our study included 25 consecutive patients who received treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…DOX also up-regulates the expression of cell surface membrane death receptors (DR), such as Fas cell surface death receptors, DR4, and DR5, TNF receptor 1 (TNFR1) in cardiomyocytes ( Zhao and Zhang, 2017 ). In addition, DOX induces the expression of toll-like receptors (TLR) that play an important role in cardiac damage via activating pro-inflammatory NFκB ( Pop-Moldovan et al, 2017 ). All these DOX-induced immune responses contribute to the activation of a caspase cascade.…”
Section: Cellular and Molecular Targets Of Doxmentioning
confidence: 99%
“…DOX also up-regulates the expression of cell surface membrane death receptors (DR), such as Fas cell surface death receptors, DR4, and DR5, TNF receptor 1 (TNFR1) in cardiomyocytes ( Zhao and Zhang, 2017 ). In addition, DOX induces the expression of toll-like receptors (TLR) that play an important role in cardiac damage via activating pro-inflammatory NFκB ( Pop-Moldovan et al, 2017 ). All these DOX-induced immune responses contribute to the activation of a caspase cascade.…”
Section: Cellular and Molecular Targets Of Doxmentioning
confidence: 99%
“…We speculate that TLR2 and TLR4 have the same signal (MyD88-dependent) pathway in new-onset atrial fibrillation patients after acute myocardial infarction. 28,29) As past studies have indicated, new-onset AF after MI is most dependent on infarction size, and AF also could cause harmful cardiovascular events and high mortality. A blood sample is collected before reperfusion therapy and patients only received aspirin, plavix, and statins.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs are members of the interleukin-1 receptor family (IL1) and are involved in the ability to react to molecular triggers associated with pathogenic microorganisms. Recent studies have shown that TLRs are activated by endogenous signals, such as heat shock proteins and oxidative stress, which can contribute to congestive heart failure 6 .…”
Section: Tlr4mentioning
confidence: 99%
“…Oxidative stress is one of the major effects in Dox-induced cardiac dysfunction. In a previous study, we hypothesized and showed that TLRs contribute to the pathogenesis of Dox-induced cardiac dysfunction via an inflammation-induced mechanism 6 . These studies also indicate that free radicals play an important role in Dox-induced CTX.…”
Section: Tlr4mentioning
confidence: 99%